Analisis Kualitas Produk dan Kepuasan Pelanggan Terhadap Pelayanan Indihome di Jakarta Pusat - Putra, Resky Illahi Dwi; Aji, Achmad Maezar Bayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
PT. Telkom (Telekomunikasi Indonesia) is a state-owned enterprise that has an important contribution to society because it is engaged in telecommunications services. Indihome is one of the service products from PT. Telekomunikasi Indonesia, which provides packages of landline, internet, and television services. In an effort to provide information services, it is necessary to evaluate the performance of internet services so that the service provider is able to maintain performance and improve performance where there are still shortcomings in performance from the user's point of view. To determine the level of service performance, this research was carried out by applying the servqual method and Importance Performance Analysis. The assessment of user satisfaction is based on five dimensions, namely Reliability, Responsiveness, Assurance, Empathy and Tangibles which later on each attribute performance will be classified into quadrant I which is the main priority to improve its service, quadra II attributes that need to be maintained because they have provided satisfactory service, quadrant III attributes that have low priority and quadrant IV attributes that are considered less important but have good performance. The results of this study indicate that the largest gap or gap lies in the Responsiveness dimension with a value of -1.00 and the smallest gap in the Empathy dimension with a value of -0.43. while based on the calculation of the Importance Performance Analysis the overall user suitability level is 83% which means that the services provided by the agency/company are in accordance with the user's perception. Where the user's perception of website services has been fulfilled